Third international conference on software, services and semantic technologies S3T 2011 - Dicheva, Darina; Markov, Zdravko 1956-; Stefanova, Eliza 1968- (Advances in intelligent and soft computing, 2011)
This volume contains the Proceedings of The Third International Conference on Software, Services & Semantic Technologies (S3T) held in Bourgas, Bulgaria on September 1-3, 2011. It is the third S3T conference in a series of annually organized events supported by the F7 EU SISTER Project and hosted by Sofia University. The conference is aimed at providing a forum for researchers and practitioners to discuss the latest developments in the area of Software, Services and Intelligent Content and Semantics. The conference sessions and the contents of this volume are structured according to the conference track themes: Intelligent Content and Semantics (10 papers), Knowledge Management, Business Intelligence and Innovation (4 papers), Software and Services (6 papers), and Technology Enhanced Learning (9 papers). The papers published in this volume cover a wide range of topics related to the track themes. Particular emphasis is placed on applying intelligent semantic technologies in educational and professional environments with papers in the areas of Ontologies and Semantic Web Technologies, Web Data and Knowledge, Social Networks Analysis, Information Extraction and Visualisation, Semantic Search and Retrieval, E-learning, and User Modelling and Personalization.